2020
DOI: 10.1093/bioinformatics/btaa285
|View full text |Cite
|
Sign up to set email alerts
|

COVID-2019-associated overexpressed Prevotella proteins mediated host–pathogen interactions and their role in coronavirus outbreak

Abstract: Abstract Motivation The outbreak of COVID-2019 initiated at Wuhan, China has become a global threat by rapid transmission and severe fatalities. Recent studies have uncovered whole genome sequence of SARS-CoV-2 (causing COVID-2019). In addition, lung metagenomic studies on infected patients revealed overrepresented Prevotella spp. producing certain proteins in abundance. We performed host–pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 20 publications
2
58
1
Order By: Relevance
“…It was found that over-expressed Prevotella proteins can promote viral infection. As per the results, Prevotella proteins, rather than viral proteins, are involved in increasing clinical severity of COVID-2019, i.e., Prevotella plays role in COVID- 2019 outbreak and attention should be paid to understanding disease mechanisms and improving treatment outcomes ( Khan and Khan, 2020 ).…”
Section: Interaction Between Oral Microbiome and Virus Infectionmentioning
confidence: 97%
“…It was found that over-expressed Prevotella proteins can promote viral infection. As per the results, Prevotella proteins, rather than viral proteins, are involved in increasing clinical severity of COVID-2019, i.e., Prevotella plays role in COVID- 2019 outbreak and attention should be paid to understanding disease mechanisms and improving treatment outcomes ( Khan and Khan, 2020 ).…”
Section: Interaction Between Oral Microbiome and Virus Infectionmentioning
confidence: 97%
“…Two of the main purposes of the authors who used proteomics were to elucidate the mechanism of host–pathogen interactions, its association with the severity of COVID-19, and to find possible therapeutic targets. Khan and Khan ( 26 ), predicted the interaction of the receptor ACE2, which is mainly expressed on the surface of airway epithelium and parenchyma of lung, with the glycoprotein found on the surface of SARS-CoV-2. Also, these authors suggest a possible role of Prevotella in the severity of COVID-19 by increasing severity of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The HPI plays an important role in the pathogenesis of any infectious organisms, but their role is more prominent in viral pathogenesis due to their reliance on effective utilization of host machinery for establishing the infection. The role of HPIs in coronavirus infections is also discussed earlier [ 12 ], but computational study of host–pathogen protein–protein interactions is adding more value for understanding the pathogenesis of coronavirus [ 13 ]. BioGrid is a well-known database of protein, genetic and chemical interactions between various organisms and host.…”
Section: Discussionmentioning
confidence: 99%